Change in Food Consumption Behavior During the COVID-19 Pandemic in Surakarta City - Girsang, Putri Feronika; Toiba, Hery; Syafrial, Syafrial (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 17 No 1 (2023): Vol 17 No 1 (2023), 2023)
The uncontrolled COVID-19 transmission has changed the socio-demographic conditions of households in Surakarta City. These changes influenced households’ decisions on spending and consumption due to the implementation of social distancing and mobility restriction policies. Thus, this study aims to (1) identify the socio-demographic characteristics of households, (2) identify food shopping and consumption patterns of households due to COVID-19 and the implementation of the PSBB policy, and (3) estimate the relationship between socio-demographic conditions and food shopping and consumption patterns during the COVID-19 pandemic in Surakarta City. This study collected data from 120 respondents through an online survey from August 2021 to September 2021. The results indicated that households reduced food purchases, often bought food from local stores, and often shopped in small stores. Meanwhile, the change in consumption patterns was the increased frequency of in-home activities, namely eating alone or with family and sparing time to improve cooking habits at home. Through chi-square analysis, changes in households’ shopping and consumption patterns were found to be significant to some socio-demographic characteristics, including age, education level, income, and occupation. The results of this study can provide information to the government to design evidence-based policies during post-pandemic recovery in Surakarta City